The course “Nonlinear Control System” cultivates students' digital literacy path under the digital transformation of education - Huang, Zixin; Zou, Die; Zhou, Yi; Li, Ziqian; Zhou, Hongjian (Frontiers in Education, 2026)
IntroductionWith the development of modern information technologies, the deep integration of digital technology and teaching in educational settings has become an inevitable trend. This study utilizes the “Nonlinear Control System” course at Wuhan Institute of Technology, a public university in China, as a teaching experiment to explore and practice the pathway for enhancing the digital literacy of postgraduates in the context of educational digital transformation. In the context of the digital economy, the course faces three major challenges: (1) weak foundational support and a disordered digital environment; (2) outdated curriculum reform and the absence of a digital classroom; (3) lack of digital practices and weak skills literacy.MethodsThis study is mainly based on the Integrated Technology of Subject Teaching Knowledge (TPACK) framework, exploring and proposing paths to enhance the digital literacy of postgraduate students from four aspects: (1) build foundational digital tool application skills upon technological knowledge (TK); (2) construct a digital learning ecosystem oriented by pedagogical knowledge (PK); (3) achieve disciplinary transfer of digital literacy with content knowledge (CK) as the carrier; and (4) promote the advanced development of digital literacy with TPACK integration ability as the core. Adopting action research (March–July 2025), data were collected via questionnaires (57 distributed, 96.5% valid), semi-structured interviews (10 students), and learning artifacts.ResultsThe questionnaire showed good reliability (Cronbach's α= 0.87) and validity (expert-reviewed). Results indicated 81.82% of students were “very satisfied” with digital teaching, 72.73% “proficient” in tools (e.g., MATLAB), and 78.18% found digital literacy “very useful” for learning.DiscussionThis study confirms the digital teaching model's effectiveness in improving postgraduates' literacy and provides references for educational digital transformation.